2007
DOI: 10.1002/eat.20432
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase and other serum liver enzymes in underweight outpatients with eating disorders

Abstract: Abnormalities in serum liver enzymes are common in outpatients with eating disorders plus underweight. CHE might be considered as a marker of the effects of primary malnutrition on liver function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…These alterations have been already reported in literature [3,61] and represent both a clinical adaptation and a marker of the effects of starvation and malnutrition.…”
Section: Discussionmentioning
confidence: 61%
“…These alterations have been already reported in literature [3,61] and represent both a clinical adaptation and a marker of the effects of starvation and malnutrition.…”
Section: Discussionmentioning
confidence: 61%
“…Reduced plasma cholinesterase activity was reported in diseases associated with injury of the hepatic parenchyma [37, 38] such as liver fibrosis, hepatitis and cirrhosis [39]. Individuals with confirmed liver cirrhosis present a 5-fold lower level of BChE than healthy controls [1].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the fall of enzyme activity is more pronounced in liver cirrhosis patients than in hepatitis patients [38]. Moreover, cholinesterases have been considered as a useful marker of the effect of primary malnutrition on hepatic function [39]. …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, certain eating disorders can cause transaminitis, including anorexia, bulimia and eating disorder not otherwise specified [29][30][31]. However, a large study of patients with eating disorders determined that hepatic dysfunction was not common among eating disorders and liver damage could often be attributed to low weight [32].…”
Section: Discussionmentioning
confidence: 99%